Acute airway obstruction by a mucus plug in a patient with a 12-year history of inserting a double cannula tracheostomy tube: A case report. (May 2022) - Miyata, Jun; Dateoka, Kaname; Yoshioka, Tetsuya
Acute airway obstruction long after tracheostomy has rarely been reported. An 81-year-old Japanese woman with a tracheostomy tube for 12 years developed a 2-day history of coughing-up sputum with difficulty, foreign body sensation, and mild dyspnea. Dyspnea worsened immediately after computed tomography, showing soft tissue opacity between the tip of the tracheostomy tube and the bronchi. A movable mass in the trachea, identified as mucus by pathological examination, was removed using bronchoscopy. Acute airway obstruction by a mucus plug potentially occurred with a long history of insertion of a tracheostomy tube. Emergency imaging studies and bronchoscopy were useful for management.